Propuesta De Gobierno De Datos Para Los Procesos De Admisiones De La Universidad Politécnico Grancolombiano (2024)
Today, organizations are experiencing a paradigm shift in data administration and management, necessitating the adoption of various standards and processes to ensure effective governance. This document presents a data governance proposal for the Universidad Politécnico Grancolombiano, emphasizing principles of quality, security, and availability, grounded in the DAMA-DMBOK (Data Management Body of Knowledge) framework. The study primarily reveals a lack of policies aligned with DAMA standards and a significant gap between the current and desired state in terms of policies, procedures, roles, and responsibilities. To bridge this gap, the proposal includes a defined structure of roles and responsibilities, along with management policy guidelines to support its implementation.